Oxido-bridged neurosteroid analogues. Synthesis of 2,19-oxido-allopregnanolone - Eduardo, S.L. (2003)
3α-Hydroxy-2,19-oxido-5αH-pregnan-20-one was synthesized in 6 steps from the easily available 19-hydroxypregnenolone 3-acetate. The 2,19-oxido bridge was formed in a single step upon spontaneous cyclization and desilylation of a TBDMS protected 19-hydroxy-2α,3α-epoxypregnane. The 4,19-oxido analogue was obtained as a byproduct upon cyclization of the isomeric 3α,4α-epoxide.